Palinomorfos del cuaternario sobre el valle del rio San Eugenio (Risaralda, Colombia) (2012)
ABSTRACT: Quantitative analysis of the palynological observations in an archaeological settlement between Late Pleistocene to Early Holocene in Santa Rosa de Cabal, Risaralda Colombia. A total of 71 samples were analysed over volcanic soils La pochola01 (47 samples) and La pochola02 (25 samples). The radiocarbon result dated the oldest simple which is 13.540±60 years B.P in the 105 cm (Late Pleistocene) and the earliest simple which was 6743±45 years B.P in the 57 cm, (Early Holocene). Diversified, well preserved palynofloras were recognized. A total of 61 species were described, including species of the, Pteridophytos (11 species), Pinopsida (1species) and Angiosperm (50species). This paper aims to contribute an increase to the knowledge of the Quaternary palynoflora in the middle Cauca.